Emotional susceptibility trait modulates insula responses and functional connectivity in flavor processing - Ebisch, Sjoerd J. H.; Bello, Annalisa; Spitoni, Grazia F.; Perrucci, Mauro G.; Gallese, Vittorio; Committeri, Giorgia; Pastorelli, Concetta; Pizzamiglio, Luigi (Frontiers in Behavioral Neuroscience, 2015)
The present study aimed at investigating the relationship between Emotional Susceptibility (ES), an aspect of the personality trait Neuroticism, and individual differences in the neural responses in anterior insula to primary sensory stimuli colored by affective valence, i.e. distasting or pleasantly tasting oral stimuli. In addition, it was studied whether intrinsic functional connectivity patterns of brain regions characterized by such differential responses could be related to ES. To this purpose 25 female participants underwent functional magnetic resonance imaging scanning, while being involved in a flavor experiment. During the experiment, flavor stimuli were administered consisting of small amounts of liquid with a different affective valence: neutral, pleasant, unpleasant. The results showed that individual differences in ES trait predicted distinct neural activity patterns to the different stimulus conditions in a region of left anterior insula that a previous meta-analysis revealed to be linked with olfacto-gustatory processing. Specifically, low ES was associated with enhanced neural responses to both pleasant and unpleasant stimuli, compared to neutral stimuli. By contrast, high ES participants showed equally strong neural responses to all types of stimuli without differentiating between the neutral and affective stimuli. Finally, during a task-free state, high ES trait appeared also to be related to decreased intrinsic functional connectivity between left anterior insula and left cerebellum. Our findings show that individual differences in ES are associated with differential anterior insula responses to primary sensory (flavor) stimuli as well as to intrinsic functional cortico-cerebellar connectivity, the latter suggesting a basis in the brain intrinsic functional architecture of the regulation of emotional experiences.